2022
DOI: 10.3390/vaccines10020182
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Response after Vaccination in Patients with Cancer—Review on Past and Present Experiences

Abstract: Patients with cancer are at particular risk for infection but also have diminished vaccine responses, usually quantified by the level of specific antibodies. Nonetheless, vaccines are specifically recommended in this vulnerable patient group. Here, we discuss the cellular part of the vaccine response in patients with cancer. We summarize the experience with vaccines prior to and during the SARS-CoV-2 pandemic in different subgroups, and we discuss why, especially in patients with cancer, T cells may be the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“…Vaccination is an established, simple, safe, and effective way of protecting people against ID [ 10 ]. Upon vaccination, regulatory T cells (Tregs) are produced, which differentiate further into specific cells to trigger cell-mediated immunity (CD8 + ) or antibody-mediated immunity (CD4 + ) [ 11 ]. The time course of the Treg response to vaccination depends on the presence of immunologic memory, which, if it exists, may activate Treg within 1–2 days [ 12 ], while the Treg-induced protection is variable and can be as short as six months, even though, in some cases (i.e., herpes zoster vaccine), this can be extended to three years [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination is an established, simple, safe, and effective way of protecting people against ID [ 10 ]. Upon vaccination, regulatory T cells (Tregs) are produced, which differentiate further into specific cells to trigger cell-mediated immunity (CD8 + ) or antibody-mediated immunity (CD4 + ) [ 11 ]. The time course of the Treg response to vaccination depends on the presence of immunologic memory, which, if it exists, may activate Treg within 1–2 days [ 12 ], while the Treg-induced protection is variable and can be as short as six months, even though, in some cases (i.e., herpes zoster vaccine), this can be extended to three years [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon vaccination, regulatory T cells (Tregs) are produced, which differentiate further into specific cells to trigger cell-mediated immunity (CD8 + ) or antibody-mediated immunity (CD4 + ) [ 11 ]. The time course of the Treg response to vaccination depends on the presence of immunologic memory, which, if it exists, may activate Treg within 1–2 days [ 12 ], while the Treg-induced protection is variable and can be as short as six months, even though, in some cases (i.e., herpes zoster vaccine), this can be extended to three years [ 11 ]. Given that exercise may improve immune system through Treg subpopulation increases [ 13 ] and interleukin-10 levels, which affects tissue homeostasis by limiting host immune response to pathogens [ 14 ], it is logical to hypothesize that it can boost the immune responses to vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…In this extensive review, the authors emphasize the fact that various clinical studies have already shown that the antigen-specific T-cell response after vaccination is more robustly and reliably induced in this vulnerable population than the antibody response [9][10][11]. Moreover, Rüthrich and colleagues underline the fact that compared to the humoral vaccine response, T cells are more likely to be cross-reactive to influenza strains or SARS-CoV-2 variants that differ from the vaccination strains or strains that caused a prior infection [1,12,13]. Thus, the authors conclude that in particular, T-cell vaccine-induced immune responses might be reliable markers for protection, which should be considered in the development of novel vaccines, especially for patients who have impaired immune responses [1].…”
mentioning
confidence: 99%
“…For decades, the measurement of specific antibodies produced in response to vaccination was the surrogate marker for protection against vaccine-preventable diseases. While clinicians still rely on the humoral response when assessing responses to a vaccine, the cellular immune response has been attracting an increasing amount of attention in recent years, most prominently since the SARS-CoV-2 pandemic [1][2][3]. In immunocompromised patients, especially those who are severely immunosuppressed from procedures such as stem cell transplantation or solid organ transplantation with life-long immunosuppression, the antibody response to vaccination is usually strongly diminished [4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation